The Determinant of Intention to Purchase - Bagus Saputro, Dito; Kurniawati (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to examine the antecedents of online purchase intentions. The data collection method used a questionnaire with a purposive sampling technique on 202 respondents who had made online purchases in the past six months. The data analysis tool that is used is the Structural Equation Model (SEM) through the AMOS and SPSS programs, while the reliability test is Cronbach’s Alpha. This study resulted in indicating that trust and ease of use have a positive impact on satisfaction. Furthermore, trust has a negative impact on the intention to purchase. Meanwhile, ease of use and satisfaction have a positive impact on the intention to purchase. Later then, there is a positive impact on intention to purchase, mediated by satisfaction, due to trust and ease of use. Managerial implications in this research are that the company must provide product review services, perform maintenance, provide the latest products, and provide rewards for its customers.